2017
DOI: 10.1002/lary.26710
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of nasal cannula versus microphone for detection of snoring

Abstract: 2b. Laryngoscope, 127:2886-2890, 2017.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
0
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
1
0
0
1
Order By: Relevance
“…Finally, we confirmed the results of previous studies that showed that snore measurements should be audio‐based, and suggested that the use of the cannula as a snore sensor be discontinued (Arnardottir et al, 2016; Pérez‐Warnisher et al, 2017) even if this measurement is linked to subjective loudness of snoring to some degree. The significant positive correlation between percentage of objective snoring and both nasal MCA and corrected nasopharyngeal volume is another argument that nasal obstruction is a bias for snoring frequency assessment.…”
Section: Discussionsupporting
confidence: 88%
“…Finally, we confirmed the results of previous studies that showed that snore measurements should be audio‐based, and suggested that the use of the cannula as a snore sensor be discontinued (Arnardottir et al, 2016; Pérez‐Warnisher et al, 2017) even if this measurement is linked to subjective loudness of snoring to some degree. The significant positive correlation between percentage of objective snoring and both nasal MCA and corrected nasopharyngeal volume is another argument that nasal obstruction is a bias for snoring frequency assessment.…”
Section: Discussionsupporting
confidence: 88%
“…En la presente investigación no es clara la coincidencia entre los datos reportados por los pacientes (subjetivos) y la aplicación móvil, en la disminución de los eventos de ronquido comparada con los resultados registrados por la polisomnografía. Estos resultados coinciden con la investigación de Hofstein, 21 quien concluyó que la percepción de los ronquidos era muy subjetiva y especuló que las investigaciones que estudiaran las consecuencias y el tratamiento del ronquido, debían emplear métodos más sofisticados y debidamente validados para medir el ronquido o, alternativamente, recurrir a mediciones de las anomalías fisiológicas subyacentes responsables del ronquido, como las elevaciones de la resistencia de las vías respiratorias superiores. Estos procedimientos que no se realizaron en el presente trabajo.…”
Section: Discussionunclassified